The relationship between leptin and periodontitis: a literature review - Guo,Zhijiao; Peng,Yanhui; Hu,Qiaoyu; Liu,Na; Liu,Qing (PeerJ, 2023)
Leptin is a peptide hormone that regulates energy balance, immune inflammatory response, and bone metabolism. Several studies have demonstrated a relationship between leptin and periodontitis, a local inflammatory disease that progressively weakens the supporting structures of the teeth, eventually leading to tooth loss. This article reviews the existing literature and discusses leptin’s basic characteristics, its relationship with periodontitis, and its effects on periodontal tissue metabolism.
Keywords: Leptin; Periodontitis; Mechanism; Inflammatory cytokines